Fortalecimiento de las destrezas en lectura comprensiva en estudiantes de sexto año de E.G.B. del Cecibeb “Juan A. Comenio”, parroquia Palmira cantón Guamote, período 2022 – 2023 - Asqui Asqui, Alonso (2023)
ABSTRACT: The objective of this research study was the design of a guide of methodological strategies aimed at improving comprehensive reading skills for sixth-grade students at the Juan A. Comenio Intercultural Bilingual Community Education Center for Basic Education. This proposal addresses the current issue of text comprehension due to poor reading skills; the impact of this issue can extend to later stages of the teaching-learning process, resulting primarily in a negative effect on academic performance in various subjects. The presented proposal aims to promote a culture of reading among students through the implementation of a series of educational activities, establishing reading as a school habit within their academic routines. The importance of this instrument lies in ensuring that the teaching-learning process adopts a new focus through the application of innovative learning methodologies, resources that are not within the purview of the teaching staff and require enhancement. To determine the initial conditions, an observation sheet was administered to the teaching staff of the institution. This instrument not only identified the teaching methods employed by the teachers but also highlighted deficiencies in the various pedagogical approaches being utilized. It was concluded that the future implementation of the proposed methodological strategies for the teaching and learning process will enhance comprehensive reading skills for the study group as well as the student population in general